Increasing Assessment of Student Learning Outcomes in Al-Qur'an Hadith Subjects Through Teaching Cognitive Strategies - Rosfiani, Okta; Zahraningtyas, Firdha; Mansyuroh, Lailatul; Syarifah, Nanda Zakiyah; Selfiani (PT. Riset Press International, 2024)
This research was motivated by observational data which showed that the acquisition of Al-Qur'an Hadith learning in the VB MI Yasiska Kedaung Pamulang class, learning model material that did not activate students and student learning outcomes were still low, so that Cognitive Strategy teaching was implemented which could improve the quality of learning. Among the appropriate learning models is Cognitive Strategy teaching which is carried out through Classroom Action Research. The method used is Classroom Action Research (PTK) which is carried out in two cycles. The research instruments used tests, group assignments, observations, field notes, and the results of discussions with observers. Data was obtained from research subjects, namely 24 students of Class VB MI Yasiska Kedaung Pamulang. The learning outcomes achieved by students in the second cycle achieved positive values. The average class score is 84. 83% (20) of students have reached and passed the KKM score of 70. This percentage has exceeded the target of 70% of students completing their studies. Students who were able to provide examples of reading Mim Sukun Law reached 19 or 79%. This percentage has also exceeded the target of 70% of students being able to demonstrate reading Mim Sukun Law. The results of the research can be concluded to be successful. Thus, the application of Cognitive Strategy Teaching can improve the assessment of student learning outcomes in the Al-Qur'an Hadith subject Legal material Mim Sukun class VB MI Yasiska Kedaung Pamulang South Tangerang.